The Transformative Implications of Technology on Accounting Practices - Shaleh, Musliha (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study examines the impact of technology integration on accounting practices, focusing on enhancing efficiency, accuracy, and accountants' evolving responsibilities. It hypothesizes that advancements in cloud computing, Artificial Intelligence (AI), and Big Data analytics improve financial reporting while introducing cybersecurity and ethical challenges. Research Design and Methodology: This research synthesizes findings from scholarly works using a systematic literature review to analyze how automation, real-time data access, and digital tools reshape financial reporting and accountants’ roles. Findings and Discussion: The study finds that technology significantly enhances efficiency and accuracy, allowing accountants to shift from data processors to strategic advisors. However, challenges such as cybersecurity risks, data privacy concerns, and the need for continuous upskilling remain critical. Implications: The findings emphasize the need to integrate technological competencies into accounting education and for policymakers to regulate responsible technology adoption. Future research should explore the long-term effects of emerging technologies on accounting ethics, governance, and regulatory frameworks to support sustainable digital transformation.